Deformation in Nisyros volcano (Greece) using differential radar interferometry - PARCHARIDIS, I. S.; LAGIOS, E. (Bulletin of the Geological Society of Greece, 2001)
Nisyros Volcano located at the southeastern Aegean Sea (Greece) has recently shown (1996-97) a high seismic activity, associated with a significant deformation has determined by DGPS measurements. The determination of the overall deformation of the island was also attempted by Differential Radar Interferometry (DInSAR). The DInSAR analysis has been applied using the ERS-2 satellite data, covering the period 1996-1999. The removal of the interferometric phase related to the topography has been done using an external high resolution DEM. Two areas of the island show a good coherence, the southwestern and the eastern part. Almost two interferometric fringes were respectively recognized and evaluated. These two zones coincide with the main tectonic fractures of the island. The time separation and resolution, which consist important factors, for the extraction of the effective information and the quality of the finally produced differential interferogram, seem however that influence very slight its accuracy. The deformation outlined by the interferogram is compatible with the existing differential GPS observations.